IDEAPHORIA eBulletin Vol 7 - Musdi, Shanat; Marzie, Hatef Jalil; Qistina Donna, Lee Abdullah; Loh, Ngiik Hoon; Natasha, Rusdy Wong; Nur Qasdina Jeeta, Abdullah; Syarafina, Abdullah; Louis Ringah, Kanyan; Aliffazraie, Jali; Candida, Jau Emang; Teo, Miaw Lee; Yow, Chong Lee; et al. (Fakulti Seni Gunaan dan Kreatif, 2023)
Greetings and welcome to the seventh edition of the FACA e-Bulletin IDEAPHORIA. The primary objective of Bulletin IDEAPHORIA, functioning as a FACA journal, is to provide a comprehensive account of the faculty's annual undertakings, encompassing projects, important occurrences of various natures, and events that foster interdisciplinary collaboration. The Faculty of Applied and Creative Arts (FACA) of the University Malaysia Sarawak (UNIMAS) has been bestowed with numerous accolades in acknowledgement of its exemplary standards of teaching and research. The recognition and honors received by the academics have significantly enhanced their national prominence, hence yielding advantageous outcomes. The faculty is dedicated to exploring innovative approaches for fostering the development of global communities in the forthcoming years. The FACA also highlights the importance of integrating academic principles into the progression of teaching as both a profession and a scholarly pursuit. The objective is to cultivate students with a comprehensive skill set that enables them to excel in the international job market upon completion of their studies, aligning with the vision of UNIMAS.